2018
DOI: 10.1002/ece3.4162
|View full text |Cite
|
Sign up to set email alerts
|

Improving geographically extensive acoustic survey designs for modeling species occurrence with imperfect detection and misidentification

Abstract: Acoustic recording units (ARUs) enable geographically extensive surveys of sensitive and elusive species. However, a hidden cost of using ARU data for modeling species occupancy is that prohibitive amounts of human verification may be required to correct species identifications made from automated software. Bat acoustic studies exemplify this challenge because large volumes of echolocation calls could be recorded and automatically classified to species. The standard occupancy model requires aggregating verifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 37 publications
1
53
0
Order By: Relevance
“…Ferguson et al (2015) recommended that researchers always use occupancy models that allow falsepositive detections, to avoid bias in estimates of occupancy. We agree, but caution that in our simulations and in those of others (Ferguson et al 2015, Clement 2016, Banner et al 2018, Chambert et al 2018a), optimal Notes: SD, standard deviation. Ψ is the probability that site is occupied during the first season, φ is the probability that an occupied site stays occupied, c is the probability that an unoccupied site becomes occupied, and fp is the probability of false detection at an unoccupied site.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Ferguson et al (2015) recommended that researchers always use occupancy models that allow falsepositive detections, to avoid bias in estimates of occupancy. We agree, but caution that in our simulations and in those of others (Ferguson et al 2015, Clement 2016, Banner et al 2018, Chambert et al 2018a), optimal Notes: SD, standard deviation. Ψ is the probability that site is occupied during the first season, φ is the probability that an occupied site stays occupied, c is the probability that an unoccupied site becomes occupied, and fp is the probability of false detection at an unoccupied site.…”
Section: Discussionsupporting
confidence: 82%
“…In conclusion, previous studies have shown, both empirically and with simulations, that even when including some level of certain detections, heterogeneity in detection and false occupancy rates can induce bias in estimates of habitat occupancy (Ferguson et al 2015, Banner et al 2018, Chambert et al 2018a). These studies also provide several methods to reduce this bias, including random sampling in study design and modeling the heterogeneity in detection parameters through covariates.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Automated detection methods may fail to detect sounds issued by species of interest (false negatives), or mistakenly detect false alarms not issued by the target species (false positives; Acevedo, Corrada‐Bravo, Corrada‐Bravo, Villanueva‐Rivera, & Aide, ; Balantic & Donovan, ; Buxton & Jones, ; Duan et al, ; Marques et al, ). Occupancy modeling frameworks are a well‐established approach for accommodating the detection mistakes that arise from remote acoustic monitoring and can deal both with false negatives (Cerqueira & Aide, ; Furnas & Callas, ; Rich, Beissinger, Brashares, & Furnas, ) and false positives (Balantic & Donovan, ; Banner et al, ; Chambert, Miller, & Nichols, ; Chambert, Waddle, Miller, Walls, & Nichols, ). However, false negatives due to suboptimal automated detection methodologies are distinct from false negatives that occur as a consequence of deficient audio sampling schedules.…”
Section: Introductionmentioning
confidence: 99%